2011 International Electron Devices Meeting 2011
DOI: 10.1109/iedm.2011.6131504
|View full text |Cite
|
Sign up to set email alerts
|

3D copper TSV integration, testing and reliability

Abstract: Node-agnostic Cu TSVs integrated with high-K/metal gate and embedded DRAM were used in functional 3D modules.Thermal cycling and stress results show no degradation of TSV or BEOL structures, and device and functional data indicate that there is no significant impact from TSV processing and/or proximity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(34 citation statements)
references
References 7 publications
1
32
0
1
Order By: Relevance
“…The IR interferometer and total thickness gauges measured silicon substrates of known thickness as certified by an accredited third party and were compared. The via-middle process scheme for TSV 3DIC fabrication holds significant interests from the semiconductor industry [1]. In this scheme, blind vias are fabricated on the deviceside of TSV wafers after completing the front-end processes.…”
Section: Measurement Using Ir Reflectancementioning
confidence: 99%
“…The IR interferometer and total thickness gauges measured silicon substrates of known thickness as certified by an accredited third party and were compared. The via-middle process scheme for TSV 3DIC fabrication holds significant interests from the semiconductor industry [1]. In this scheme, blind vias are fabricated on the deviceside of TSV wafers after completing the front-end processes.…”
Section: Measurement Using Ir Reflectancementioning
confidence: 99%
“…In order to understand and mitigate thermal fatigue concerns in Cu TSV interconnects, many studies have been reported that have assessed the thermal cycling effect on their reliability performance [2], [3], [4], [5]. These reported studies were focused on understanding how thermal cycling impacts the electrical characteristics of Cu TSVs, as well as the use of focused ion beam (FIB) and scanning electron microscopy (SEM) failure analysis tools to identify damage growth and propagation.…”
Section: Introductionmentioning
confidence: 98%
“…What follows is a brief summary of the motivation for why those particular methods have been preferred. First, via-first [8]- [10] and viamiddle [11], [12] type TSVs can only be fabricated in a CMOS foundry. Therefore, via-last approach is preferred to develop 3-D prototypes in a MEMS clean room after the pretesting and selection of working chips (known-good-die or KGD).…”
Section: Introductionmentioning
confidence: 99%